Investigating the in-flight droplets' atomization in suspension plasma-sprayed coating. (January 2022) - Dalir, E.; Dolatabadi, A.; Mostaghimi, J.
Highlights: A plasma spraying model, including electromagnetic fields, is applied to investigate the in-flight droplets' fragmentation. The proposed model is implemented on the ANSYS-Fluent commercial software. A dynamic drag law is added to the developed model to consider the droplets' shape. The effects of Kelvin-Helmholtz, Rayleigh-Taylor instabilities, and liquid core length on droplets' atomization are analyzed. Validation is performed by comparing the results with the existing data. Abstract: A three-dimensional unsteady numerical model is employed to study the in-flight droplets/particles' atomization in the suspension plasma spraying (SPS) process. A user-defined function (UDF) written in C programming adds the electromagnetic fields to the fluid flow field. A two-way coupled Eulerian-Lagrangian technique simulates the sprayed droplets' interaction with the plasma flow. The developed model is applied to investigate the droplets' atomization behavior in the SPS process. Droplets' atomization is simulated by applying the Kelvin-Helmholtz Rayleigh-Taylor (KHRT) breakup model. This model considers the effects of both aerodynamic forces (Wave model) and Rayleigh-Taylor instabilities on the atomization process combing a liquid core region (Levich model). Previous works to estimate the KHRT breakup model's coefficients were performed on a liquid jet ( e.g., fuel jet) into the air. Because the density ratio of suspension in the plasma is higher than that of the liquid jet into the air (suspension density is higher than a liquid droplet and plasma density is lower than air), the model's coefficients should be modified for the suspension atomization in the SPS process. For this reason, nine case studies are investigated to see the effect of KH and RT instabilities and the liquid core length on the droplets/particles' atomization. The results obtained from the suggested values show a good agreement compared to the existing data.